USING SOCIOGRAM TO IMPROVE THE WRITING AND SPEAKING ACHIEVEMENTS OF THE EIGHT GRADE STUDENTS OF SMPN 1 JARAI - Pratama, Yoga (Universitas Muhammadiyah Palembang, 2018)
The objectives of this study were to find out whether or not there was significant improvement in writing and speaking achievements of the eighth grade students of SMPN1 Jarai after they were taught by using Sociogram, to find out whether or not there was significant improvement in each aspect of writing and speaking achievements of the eighth grade students of SMPN1 Jarai after they were taught by using Sociogram, to find out whether or not there was significant difference in writing and speaking achievements between the eighth grade students of SMP 1 Jarai who were taught by using Sociogram and those who were not, and to find out the perception of the eighth grade students of SMPN 1 Jarai after they were taught by using Socoiogram. In this paper, an experimental research method with pre and post test control group design was used with 70 students as the sample divided into two groups, experimental and control group. However, only the students of the experimental group were taught by using Sociogram. The obtained data were analyzed by using t-test. The students were given questionnaire to know their perceptions. The result showed that there was a significant difference in both students? writing and speaking achievements after they were tought by using Sociogram. Furthermore, it was found that there was a significant difference in students? writing and speaking achievement between the experimental and control groups. In conclusion, Sociogram improves the students? writing and speaking achievements.